2022
DOI: 10.4103/jmas.jmas_338_21
|View full text |Cite
|
Sign up to set email alerts
|

Graphical education and appropriate time before elective colonoscopy make better bowel preparation

Abstract: Background: Inadequate bowel preparation leads to lower polyp detection rates, longer procedure times and lower cecal intubation rates. However, there is no consensus about high-quality bowel preparation, so our study evaluated graphical education and appropriate time before elective colonoscopy. Patients and Methods: We performed a secondary analysis of a national colorectal cancer screening programme of 738 patients. The patients were divided into a group given a grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Elderly persons may not benefit from printed directions, and as a result, different randomized controlled trials have shown the benefits of pre-endoscopy education. Patients who received a personalized booklet [ 23 ], animated visual educational training [ 24–26 ], smart phone applications, or instructional video clips had better bowel cleansing, regardless of the laxative used [ 27 ]. Video re-education was generally effective but varied based on the patient’s age, the purgative used, and the educational material shown [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elderly persons may not benefit from printed directions, and as a result, different randomized controlled trials have shown the benefits of pre-endoscopy education. Patients who received a personalized booklet [ 23 ], animated visual educational training [ 24–26 ], smart phone applications, or instructional video clips had better bowel cleansing, regardless of the laxative used [ 27 ]. Video re-education was generally effective but varied based on the patient’s age, the purgative used, and the educational material shown [ 28 ].…”
Section: Introductionmentioning
confidence: 99%